(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
One of the several normal-flora of an individual’s vaginal, oral cavity, gastrointestinal tract and mucosal membrane are Candida species. Candida have been associated with diverse diseases including life threatening invasive, superficial and hematogenic infections. This study determined the prevalence of Candida species amongst unmarried women attending Lafia Primary Health Care Centers. Forty high vagina swabs were collected from unmarried women. Isolation and identification of Candida species were performed according to standard procedures using Sabouraud Dextrose Agar, Gram staining and Germ tube test. 13 (32.5%) were positive for five different Candida species. C. albicans was the most prevalent (38.46%; 5/13) species while non-albicans Candida [C. glabrata (23.07%; 3/13), C. tropicalis (6.89%; 2/13), C. parapsilosis (3.44%; 1/13) and C. krusei (6.89%; 2/13)] accounted for 61.54% (8/13) of the total positive cases. Women aged 15-18 years and 23-26 years had the lowest and highest prevalence rates of 14.28% (1/7) and 42.10% (8/19) respectively. Candidiasis is a threat to global health and should be taken with all seriousness. The high candidiasis prevalence observed herein portrays a concern and calls for a continuous study of unmarried women attending Primary Healthcare Centers in Lafia. Furthermore, there should be an improvement in creating awareness of the opportunistic pathogenic characteristic of Candida species as normal flora and the effect they cause when there are hormonal imbalances caused by drug abuse, pregnancy, and poor dieting. The practice of good hygiene should be observed to prevent the spread of the infection.